Factors purchasing patterns of eco-friendly cosmetics and beauty care products / Siti Syuhada Ab Azib - Ab Azib, Siti Syuhada (Faculty of Business and Management, 2019)
Malaysia is one of the countries in the emergent country stages. Align with that, going natural is a growing trend. Nowadays, consumers becoming more and more conscious of what they put in and on their bodies. The purpose of this study is to explore the purchasing patterns of eco-friendly cosmetics and beauty care products among lecturers and staffs in UiTM Bandaraya Melaka. It also investigates upon the relative consequence of these factors in predicting the liking to buy and recommend eco-friendly cosmetics and beauty care products to others. The research design for this study will using simple random sampling on a sample of 97 female lecturers and staffs of UiTM Bandaraya Melaka from the total population of 131 and connect them with eight factors influencing the purchasing patterns of eco-friendly and beauty care products namely: “women lifestyles, self-image health and economic considerations”, “ethical consumerism among females”, “pharmacological essence of green cosmetics and beauty care products”, “visual appeal and physical cues in cosmetic stores”, “price conscious decisions and effective promotion”, “belief on ethical claims in green messages”, “brand image and usage experience” and “sales representatives and social influencers”. Overall, based on Model Summary the most influence factor influencing on purchase patterns for eco-friendly cosmetics and beauty care products is ethical consumerism among females. The finding of this study would provide useful insights for the factors purchasing patterns of eco-friendly cosmetics and beauty products among female consumers.